Deposition and Characterization of Nanoparticles MnO2 Thin Films on Aluminium Coated Plastic Substrate for Electrochemical Applications - Tan, Caryn Hui Chuin (Universiti Malaysia Sarawak (UNIMAS), 2015)
Manganese dioxide, (MnO2) nanoparticles have been well-known to be deposited as thin-film materials because of its superior optical, electrical, catalytic, electrochemical properties and magnetic. Researchers had used many instruments in order to characterize physical properties of MnO2 nanoparticles and deposited thin films. In this project, UV Visible spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), Atomic Absorption Spectrometer (AAS) and Energy Dispersive X-ray Spectroscopy (EDX) were used to characterize MnO2 nanoparticles and deposited thin films. Stable MnO2 colloidal suspension will be synthesized by 2 techniques. The deposition of MnO2 thin film on aluminium coated plastic substrate were conducted by electrophoretic deposition method by using a Scribner cell. Deposition parameters such as different voltage and time were used to investigate the thickness of manganese dioxide deposited on the substrate. The electrochemical properties of deposited MnO2 films were studied.